Upaya Meningkatkan Hasil Belajar Tema Panas dan Perpindahannya Muatan Pembelajaran IPA melalui Metode Student Case Study Berbasis Video pada Siswa Kelas V Sdn 1 Merbuh - Wahyuni, Wahyuni (Persatuan Guru Republik Indonesia Kota Semarang, 2023)
This research was motivated by the low learning outcomes of students in learning the theme of Heat and the Transfer of Science Learning Content in class V of SDN 1 Merbuh, Singorojo District, Kendal Regency, semester 2 of the 2022/2023 academic year. Student learning completion that has not reached the minimum percentage determined by the school. The application of the video-based Student Case Study method has the potential to actively involve students in learning. Thus, student learning outcomes are expected to increase according to expectations. This research aims to determine whether the application of the video-based Student Case Study method can improve learning outcomes on the theme of Heat and Transfer in science lesson content. This research consists of 2 cycles with 3 meetings in each cycle. Learning refers to the steps in applying the video-based Student Case Study method that has been prepared previously. The learning process for the theme of Heat and the Transfer of Science lesson content from cycle I to cycle II has increased in a direction that is conducive, enjoyable and meaningful. Student learning outcomes through the application of the video-based Student Case Study method have increased significantly. In pre-cycle learning there were 11 out of 22 students or a complete score or 50.00%, in Cycle I improvement this increased to 15 students or 68.18%, in Cycle II improvement it increased to 20 students or 90.91%. The learning outcomes obtained are in accordance with the predetermined success indicators, namely 2. A total of ≥ 85.00% of students can achieve the Minimum Completeness Criteria (KKM) in the learning theme of Heat and Transfer that has been determined by the school, namely 70.00 with an average score of - class average ≥ 75.00.